2002
DOI: 10.1136/ip.8.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Role of individual and contextual effects in injury mortality: new evidence from small area analysis

Abstract: Objective: To analyse the role of individual and contextual variables in injury mortality inequalities from a small area analysis perspective, looking at the data for the city of Barcelona (Spain) for 1992-98. Setting: Barcelona (Spain). Methods: All injury deaths in residents older than 19, which occurred in the period 1992-98 were included (n=4393). Age and sex specific mortality rates were calculated for each educational level and each cause of death (traffic injuries, falls, drug overdose, suicide, other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 44 publications
(23 reference statements)
8
32
1
2
Order By: Relevance
“…Studies on suicides have reported a positive relationship between deprivation and mortality (Burrows et al, 2010;Chang et al, 2011;Esnaola et al, 2006;Middleton et al, 2006;Miller et al, 2005), however one systematic review found that the existence of this relationship depends on the size of geographical area analysed and on the variables used to measure deprivation (Rehkopf and Buka, 2006). In the case of falls, associations have also been reported between areas of greater deprivation and mortality due to this cause (Borrell et al, 2002;Esnaola et al, 2006). Finally, studies on traffic injuries are inconclusive in this regard.…”
Section: Introductionmentioning
confidence: 91%
“…Studies on suicides have reported a positive relationship between deprivation and mortality (Burrows et al, 2010;Chang et al, 2011;Esnaola et al, 2006;Middleton et al, 2006;Miller et al, 2005), however one systematic review found that the existence of this relationship depends on the size of geographical area analysed and on the variables used to measure deprivation (Rehkopf and Buka, 2006). In the case of falls, associations have also been reported between areas of greater deprivation and mortality due to this cause (Borrell et al, 2002;Esnaola et al, 2006). Finally, studies on traffic injuries are inconclusive in this regard.…”
Section: Introductionmentioning
confidence: 91%
“…However, the relationships between these variables and suicide risk were not fully consistent: for residential mobility, family income, poverty rate, black racial concentration and poor female headed households, the significantly increased suicide risks are only observed at the intermediate levels. Borrell et al (2002) used multilevel Poisson regression models to study injury mortality including 804 suicides. After controlling for individual variables no relationship between the percentage of neighbourhood unemployment or the proportion of men in jail and suicide was observed.…”
Section: Suicide Mortalitymentioning
confidence: 99%
“…Social inequalities exist with regard to the health burden of road safety: underprivileged subjects have the highest morbidity and mortality as a consequence of crash involvement (Borrell et al 2002;Cubbin et al 2000a). …”
Section: Contextmentioning
confidence: 99%